Enriching The Students’ Vocabulary Mastery By Applying Deconstruction Analysis At STKIP YPUP Makassar - Adriani Jihad (el-Idarah: Jurnal Manajemen Pendidikan Islam, 2018)
Applying appropriate technique to develop the students’ vocabulary mastery is the English lecturer’s responsibility in STKIP YPUP Makassar to create the situation. Deconstruction analysis is a technique in generating vocabulary class more fun, enjoyable, and memorable for the students. This research aims at: (1) finding out whether or not the use of deconstruction analysis effective to develop the students’ vocabulary in word formation, word meaning and word usage and (2) knowing the aspect which is mostly affected by using deconstruction analysis. This research employed quasi experimental design. The population of this research was the students of English department at STKIP YPUP Makassar, which consisting of five classes in 2016/2017 academic year. The total number of population was 150 students. This research used cluster random sampling. The samples of this research; one class was as an experimental class and the other was as a control class. The samples of each class were 30 students. The research data was collected by using vocabulary test to get the students’ vocabulary achievement in covering word formation, word meaning and word usage, which were analyzed by inferential statistic through SPSS version 22.0 for windows program. The students’ result of post-test of experimental group is significantly developed than the students’ result of post-test of control group by the mean score 76.22 > 37.55. The difference of both scores is statistically significant based on the t-test value at significant level 0.05 in which the probability value is lower than the significant level (0.00 < 0.05). The three aspects (word formation, word meaning, and word usage) have the same average score; the score of F-Obs (1.64) was smaller than F-table (3.10) or 1.64 < 3.10. So, H1 was rejected and H0 was accepted.It can be concluded that the use of deconstruction analysis effective to develop the students’ vocabulary in word formation, word meaning and word usage. Besides, the three aspects have the same average score. It reveals that no one of the three aspects is mostly affected by using deconstruction analysis.